Routed planar networks - David J. Aldous (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2016)
Modeling a road network as a planar graph seems very natural. However, in studying continuum limits of such networks it is useful to take routes rather than edges as primitives. This article is intended to introduce the relevant (discrete setting) notion of routed network to graph theorists. We give a naive classification of all 71 topologically different such networks on 4 leaves, and pose a variety of challenging research questions.